High-Surface-Area Mesoporous Activated Carbon from Hemp Bast Fiber Using Hydrothermal Processing - Md Zakir Hossain; Wei Wu; William Z. Xu; Muhammad B. I. Chowdhury; Anil Kumar Jhawar; Devin Machin; Paul A. Charpentier (C, 2018)
Synthesis of activated carbon from waste biomass is of current interest towards sustainability. The properties of biomass-derived activated carbon largely depend on the carbonization process. This study reports the preparation of mesoporous activated carbon with extremely high surface area from hemp bast fiber using hydrothermal processing. Hot water processing (390–500 °C) followed by activation using KOH and NaOH was investigated at different mass ratios. The described approach was found to enhance the mesoporosity (centered at 3.0 to 4.5 nm) of the hemp-derived activated carbon (HAC) from activation [confirmed by BJH (Barrett-Joyner-Halenda) pore size distribution and TEM (transmission electron microscopy) imaging]. BET (Brunauer-Emmett-Teller) results showed that the product has an extremely high surface area (2425 m2/g) while the surface functional groups (–OH, –COOH, C=C/C–C) were confirmed by FTIR (Fourier transform infrared spectroscopy) and further quantified by XPS (X-ray photoelectron spectroscopy). Increasing KOH concentration was found to enhance the surface area with a maximum biochar-to-KOH (g/g) ratio of 1:3. The crystallite domain size of HAC was determined using Raman spectroscopy of different wavelengths. The procedure described in this study is an environmentally friendly scalable route for the mass production of activated carbon using hemp fiber.